Factors associated with satisfaction at work in Psychosocial Care Centers - Sonia Regina da Costa Lapischies; Vanda Maria da Rosa Jardim; Luciane Prado Kantorski (Universidade de São Paulo, 2014)
OBJECTIVES: to analyze the prevalence of satisfaction at work and identify associated factors in Psychosocial Care Centers.METHOD: cross-sectional study involving 546 workers from 40 Psychosocial Care Centers in the South of Brazil. The satisfaction was identified based on the Assessment Scale of Satisfaction in the Mental Health Team and a logistic regression model was used for the adjusted data analysis.RESULTS: the prevalence of satisfaction at work corresponded to 66.4%. Factors directly associated with satisfaction: higher-level function (except physicians and psychologists), work time of six months or less, making a larger number of home visits, good supervision by the team, possibility to make collective choices and take courses.CONCLUSIONS: the satisfaction is associated with the work organization and conditions and demonstrates the need to invest in team supervisions, in process that democratize the services and in the workers' training.